Numerical analysis of subcritical flow over two-cycle trapezoidal labyrinth side weir - Aydin, M. Cihan; Emiroglu, M. Emin (Elsevier Sci Ltd, 2016)
The side weirs are basic and effective hydraulic structures utilized commonly in irrigation, flood management, drainage and wastewater systems. The labyrinth side weirs have developed in recent years as more effective and efficient mechanism than conventional side weirs. The multi-cycle trapezoidal labyrinth side weirs could increase the side weir performance. The hydrodynamics of these weirs are considerably sophisticated due to the turbulent flow and vortices in the cycles. This paper presents the hydrodynamic behavior of the side weir with two cycles using Computational Fluid Dynamics (CFD) method. The grid convergence index (GCI) was used to demonstrate the mesh sensitivity in the results, and a fine mesh (9 mm) selected relatively among the used meshes was applied to computational volume for more accuracy. As the turbulent model, Reynolds Stress Model (RSM) model, which requires more computation effort, was implemented to consider turbulence effects in more detail. Additionally, certain experimental results were used for verification of the numerical results, and the CFD results were considerably consistent with experimental observations. The detailed hydrodynamic results, which were too hard to determine experimentally, were presented to describe the flow properties of this weir. The results indicated that the discharge coefficient decreased with an increase in Froude number. The best performances were obtained with side weir angle, alpha=30 degrees and weir height, p=20 cm among tested values. The results encouraged the use of computational fluid dynamics methods for the further analyses. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: CFD; Labyrinth side weir; Surface flow; Two cycles; Water surface profile